2017
DOI: 10.1016/j.bbmt.2017.01.073
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Bacterial Blood Stream Infections in Pediatric Allogeneic Hematopoietic Cell Transplantation Recipients: The Role of Acute Gastrointestinal Graft-versus-Host Disease

Abstract: Blood stream infections (BSI) caused by enteric organisms are associated with a particularly high mortality rate in allogeneic hematopoietic cell transplantation (alloHCT) recipients. We conducted a retrospective multicenter study aiming to analyze the risk factors associated with antibiotic resistance and impact of BSI on transplantation-related mortality (TRM) in children after alloHCT. During the study period from 2004 to 2014, 395 children (mean age, 9.4 years) with at least 1 BSI were included. The incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Data on resistance rates in post-HSCT children are scarce [12,16,29]. Surpr resistance rates were mostly similar in children and in adults in our study.…”
Section: Outcomementioning
confidence: 41%
See 2 more Smart Citations
“…Data on resistance rates in post-HSCT children are scarce [12,16,29]. Surpr resistance rates were mostly similar in children and in adults in our study.…”
Section: Outcomementioning
confidence: 41%
“…Several studies reported risk factors for cephalosporin-resistant, ESBL-pro or MDR bacteria in cancer and HSCT patients [10,12,13,16,22,29,32]. Onl handful describe risk factors for carbapenem-resistant infections in popula involving but not limited to transplant patients, mainly for K. pneumoniae.…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent BSIs in patients undergoing SCT are associated with increased mortality . To our knowledge, this is the first case series describing patients with three or more BSIs after SCT.…”
Section: Discussionmentioning
confidence: 85%
“…The majority of BSI occurs during the preengraftment period and is associated with prolonged hospitalization, intensive care unit admission, and protracted antibiotic exposure, leading to increased morbidity and mortality . In particular, it has recently been shown that patients who have more than one BSI within the first year following SCT have a higher rate of nonrelapsed mortality (NRM) than patients experiencing a single BSI …”
Section: Introductionmentioning
confidence: 99%